Livestock Owners' Perception on the Impact of Ghibe-III Hydroelectric Dam on Bovine Trypanosomosis, Southern Ethiopia - Solomon Mekuria Wudneh (SAGE Publishing, 2022)
Background: Trypanosomosis is an endemic livestock disease in Ethiopia. The problem prevails mainly in the South, Southwest, and Northwest regions following main rivers and their tributaries. Methods: A cross-sectional questionnaire survey was conducted in Loma and Kindo Didaye districts near the Ghibe-III hydroelectric dam, to compare dam impact upstream and downstream, from January 2019 to June 2020. Two hundred standardized questionnaire surveys were administered. The questionnaire included biography, livestock population before and after dam construction, knowledge of major livestock diseases, clinical signs, transmission, seasonality, and wildlife population status was assessed. Data were analyzed using Mann-Whitney U Test. Results and discussion: A total of 189 questionnaires were returned out of 200 questionnaires administered. Among the respondents, the majorities were males and had an average age of 39.4 + 10.6. In all herd size levels, there was no significant ( P  > .05) difference before dam construction between the 2 districts; whereas, statistically significant ( P  < .05) large and medium herd sizes increased by 16%(95% CI: 0.5, 31.5) after dam construction in Loma district; whereas, the same herd size reduced by 20%(95% CI:0,43.7) after dam construction with statistically significant( P  < .05) difference. Bovine trypanosomosis ranked first among major diseases. Knowledge of clinical signs, transmission, and seasonality of trypanosomosis was consistent with the literature. 87.8% of respondents in Loma associated reduction of trypanosomosis and tsetse population, but 77% of Kindo Didaye respondents perceived no change in prevalence after dam construction. More reduction in wildlife population was observed upstream than downstream, health services improved, and disease outbreaks and cattle deaths were reduced. Studies in African countries indicate the reduction in tsetse apparent density and absences of wildlife contributed to the reduction of trypanosomosis. CONCLUSION: An increased herd size, reduced trypanosomosis prevalence, and wildlife population observed upstream, indicate artificial Lake has an impact on tsetse apparent density. Therefore, follow-up of the disease prevalence and investigation of drug resistance is recommended to prove the situation in the study area.